Assessment of straight-line accuracy of an autopilot tractor with various speeds on flat area / Muhammad Hairie Hamdan - Hamdan, Muhammad Hairie (Faculty of Plantation and Agrotechnology, 2019)
New Holland tractor (TD5.75) is a vital in plantation industry because it got variety of usage in agriculture since it is complete with many equipment to improve agricultural activity such as nitrogen sensor, soil EC meter, VRA and etc. With improvement of technology, the New Holland tractor come up with the latest technology which is equip with autopilot system. The purpose of study been conducted is to measure error in each of specific level of speed as well as study of relationship between speeds and accuracy of autopilot tractor. The autopilot tractor (New Holland TD5.75) is rarely been used in Malaysia thus the stable speed that able to move forward with accurate straight line is still unknown. Currently the accuracy are totally depend on the DGPS since depending on GPS only could lead to pseudo range error. The data collection in this study was obtained through field observation at UiTM Jasin share farm where is three level of speeds, (1000 rpm, 1500 rpm, 2000 rpm) have been test and the data has been analyse using Statistical Package For Social Sciences (SPSS) version 25 and Microsoft excel 2016. The result from this study shows that, there is a significant different between three level of speeds. There is a close relationship between speeds and accuracy which is the higher the level of speeds, the lower the error occur. However, the result of study was suitable only for the flat area.